RECENT REVIEW ON ETHNOMEDICINAL, PHARMACOLOGICAL AND CHEMICAL ASPECTS OF BANANA (MUSA PARADISIACA): Review on ethnomedicine, pharmacology and chemistry of banana - Gavídia-Valencia, José G.; Venegas-Casanova, Edmundo; Hajdu, Zsanett; Rubio-López, Felipe R.; Gutiérrez-Ramos, Miriam E.; Rengifo-Penadillos, Roger A.; Sopán-Benaute, Carlos N.; Castro-Gálvez, Keila A.; Gonzales-Pósito, Gladys; Ruiz-Reyes, Guillermo S.; Albuquerque, Ricardo Diego (Food and Feed Research, 2026)
Musa paradisiaca Link (Musaceae) is not only extensively utilized in gastronomy worldwide but also holds significant relevance in ethnomedicine. This review aims to compile information regarding the traditional applications, pharmacological activities, and phytochemical constituents of this species. A systematic literature search was conducted using Scopus, ScienceDirect, PubMed Central, and Alicia databases, yielding 70 relevant documents, mainly published between 2015 and 2025. In traditional medicine, the fruit of M. paradisiaca is primarily employed for the treatment of diarrhea, whereas other plant organs exhibit diverse therapeutic functions, including wound healing and the management of diabetes and colds. Phytochemical analyses reveal that flavonoids, phenolic acids, fatty acids, calcium, and potassium constitute the principal bioactive compounds in mature fruits, while distinct metabolites are present in other plant parts. Recent in vitro and in vivo pharmacological studies have demonstrated a broad spectrum of bioactivities for M. paradisiaca, with antimicrobial, antioxidant, anti-inflammatory, antidiabetic, and wound-healing properties being the most extensively investigated. Furthermore, soluble fibers, flavonoids, tannins, and saponins have been identified as the primary bioactive compound classes responsible for these effects. In conclusion, recent ethnobotanical, phytochemical, and pharmacological research on M. paradisiaca has expanded scientific knowledge regarding its medicinal applications, providing a foundation for its appropriate utilization in various health-related fields, including nutrition, pharmacy, and medicine.
Keywords: Banana; Medicinal Use; Phytoconstituents; Diarrhea; Wound healing